Stability of laminated composites with delaminations - Yap, Chun Wee (2010)
In this thesis, investigation on buckling problem of composite beam is carried out. A new formula which is denoted as CLT method 3 is derived to calculate the effective flexural stiffness of the thin composite beam. Two other existing equations indicated as CLT methods 1 and 2 that can also be used to evaluate the effective bending rigidity are presented. Furthermore, in order to examine the buckling phenomena of moderately thick composite beam, three different collections of expressions designated as FSDT methods 1, 2 and 3 are presented to compute three separate sets of values for the effective flexural stiffness, effective shear modulus and shear correction factor in the first-order shear deformation beam theory.